Molecular Phylogeny Reveals the Past Transoceanic Voyages of Drywood Termites (Isoptera, Kalotermitidae). (3rd May 2022) - Buček, Aleš; Wang, Menglin; Šobotník, Jan; Hellemans, Simon; Sillam-Dussès, David; Mizumoto, Nobuaki; Stiblík, Petr; Clitheroe, Crystal; Lu, Tomer; González Plaza, Juan José; Mohagan, Alma; Rafanomezantsoa, Jean-Jacques; et al.
Abstract: Termites are major decomposers in terrestrial ecosystems and the second most diverse lineage of social insects. The Kalotermitidae form the second-largest termite family and are distributed across tropical and subtropical ecosystems, where they typically live in small colonies confined to single wood items inhabited by individuals with no foraging abilities. How the Kalotermitidae have acquired their global distribution patterns remains unresolved. Similarly, it is unclear whether foraging is ancestral to Kalotermitidae or was secondarily acquired in a few species. These questions can be addressed in a phylogenetic framework. We inferred time-calibrated phylogenetic trees of Kalotermitidae using mitochondrial genomes of ∼120 species, about 27% of kalotermitid diversity, including representatives of 21 of the 23 kalotermitid genera. Our mitochondrial genome phylogenetic trees were corroborated by phylogenies inferred from nuclear ultraconserved elements derived from a subset of 28 species. We found that extant kalotermitids shared a common ancestor 84 Ma (75–93 Ma 95% highest posterior density), indicating that a few disjunctions among early-diverging kalotermitid lineages may predate Gondwana breakup. However, most of the ∼40 disjunctions among biogeographic realms were dated at <50 Ma, indicating that transoceanic dispersals, and more recently human-mediated dispersals, have been the major drivers of the global distribution of Kalotermitidae. Our phylogeny also revealed that the capacity to forage is often found in early-diverging kalotermitid lineages, implying the ancestors of Kalotermitidae were able to forage among multiple wood pieces. Our phylogenetic estimates provide a platform for critical taxonomic revision and future comparative analyses of Kalotermitidae.